2009
DOI: 10.1186/2047-783x-14-2-90
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder metastasis from renal cell carcinoma mimicking acute cholecystitis

Abstract: Renal cell carcinoma constitutes about 3% of adult malignancies. It has a high metastatic potential associated with synchronous or metachronous metastatic disease. Further, it is known to metastasize mainly to the lung, bone, brain, liver, or adrenal glands. In very rare cases it can metastasize to the gallbladder mimicking acute cholecystitis on clinical exam. In this case we present a patient who developed a gallbladder metastasis five years after a renal cell carcinoma mimicking acute cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In fact, this is the first report of metastasize inside the gallbladder from a tumor of colon origin. There are few reports describing gallbladder metastasize from other origins [ 13 16 ]. The prognostic of these patients was very poor with most of them achieving <1-year survival.…”
Section: Commentsmentioning
confidence: 99%
“…In fact, this is the first report of metastasize inside the gallbladder from a tumor of colon origin. There are few reports describing gallbladder metastasize from other origins [ 13 16 ]. The prognostic of these patients was very poor with most of them achieving <1-year survival.…”
Section: Commentsmentioning
confidence: 99%
“…Metastatic disease is common, and one third of newly diagnosed cases will have synchronous metastatic disease at presentation. A further 25–50 % will develop metachronous disease [2]. Latent distant metastasis is characteristic of renal cell carcinoma (RCC) and can manifest more than a decade after nephrectomy in about 10 % of patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…The most common presenting condition appears to be cholecystitis, although cholelithiasis, jaundice, and biliary dyskinesia have also been reported as presentations. Breast carcinoma metastasis to the gallbladder is often diagnosed on histopathological examination following cholecystectomy [13–23] . After performing a search of the PubMed database, a review of 12 articles on breast carcinoma metastasis to the gallbladder revealed that the time between breast cancer diagnosis and presentation of gallbladder metastasis ranges from 1 month to 10 years [13–24] .…”
Section: Discussionmentioning
confidence: 99%